P5_7 Palpatine’s Pudding Powered Paws - Knott, George; Sharman, Mark; Rayson, Ben; Molloy, David (Physics Special Topics, 2022)
In this paper, we have calculated the number of calories Palpatine would have needed to consume in order to charge his hands to produce to force lightning used to kill Mace Windu. We find that Palpatine would have had to eat 38,334 portions of Wetherspoons Apple Crumble and Custard in order to generate the energy required to produce the force lightning. The magnitude of the value is highlighted by the fact that he would need to have 1 portion of pudding for 105 years to achieve this, showing that `The Force' must play a role since this is an unfeasible amount to eat.